Idiopathic Mandibular Osteosclerosis: A Case of Complex Diagnosis - Alexandre Perez; Avigaïl Mamane; Tommaso Lombardi (MDPI AG, 2023)
The purpose of this study is to report a case of idiopathic osteosclerosis of the mandible and to discuss the differential diagnosis of this lesion. A 17-year-old female was referred to the University Hospital of Geneva by her orthodontist following the fortuitous finding of a radio-opaque lesion in the right posterior mandible at the apex of tooth 44. Intraoral clinical examination revealed no abnormalities of the oral mucosa. Tooth 44 was asymptomatic and reacted positively to the sensitivity test. The orthopantomogram revealed a well-defined unilocular radiodense lesion, surrounded by a thin radiolucent border, measuring 10 × 33 mm, located in the IV quadrant, related to the apex of tooth 44. Differential diagnoses mainly included cementoblastoma, focal cemento-osseous dysplasia, ossifying fibroma, condensing osteitis and idiopathic osteosclerosis. The biopsy material allowed a diagnosis of idiopathic osteosclerosis. The proposed treatment was therefore a "wait and see" approach. After 2 years of follow-up, the patient was asymptomatic, and healing was complete without any neurosensory complications. Our case underlines the differential diagnosis complexity of radio-opaque lesions associated with teeth.